Time to Achieving Clinically Significant Outcomes after Meniscal Allograft Transplantation. Issue 7 (30th July 2021) - Huddleston, Hailey; Mehta, Nabil; Polce, Evan; Gilat, Ron; Alzein, Mohamad; Parvaresh, Kevin; Verma, Nikhil; Cole, Brian; Yanke, Adam
Objectives: Meniscal allograft transplantation (MAT) is a surgical treatment option for patients with meniscus deficiencies. Prior studies have defined clinically significant outcomes such as minimal clinical important difference (MCID) and patient acceptable symptomatic state (PASS) for commonly administered patient reported outcome measures (PROMs) after MAT. The purpose of this study was to determine the time to achieving MCID and PASS and to identify any risk factors affecting achievement in patients undergoing MAT. Methods: A prospectively maintained MAT registry was retrospectively reviewed from April 2014-May 2020. Patients who underwent revision MAT or did not complete preoperative PROMs were excluded. International Knee Documentation Committee (IKDC) and Knee Injury and Osteoarthritis Outcome Scores (KOOS) were administered preoperatively and at 6-months, 1-year, and 2-years postoperatively. Previously defined MCID and PASS thresholds were utilized and Kaplan-Meier survival curve analysis with interval censoring was used to calculate the cumulative percentages of MCID, and PASS achievement at each follow-up time interval (5-7, 11-13, and 23-25 months). Results: Eighty-four patients (mean age: 28.2±9.7) were included. Time to MCID and PASS is presented inTable 1 . Previously reported PASS values for KOOS Pain, Symptoms, and Sport did not reach an AUC>0.70 and thus were not included in analysis. Worker's compensation status was found to delay time to achieving MCID for all PROs (HR=0.238-0.305, P=0.008-0.020) and PASS for KOOS Symptoms (HR=0.171, P = 0.026) and IKDC (HR=1.88, P<0.001) (Table 2 and 3 ). Higher preoperative PRO score was associated with mildly delaying the time to achieving MCID for all PROs (HR=0.947-0.970, P<0.001), while higher preoperative PRO scores were associated with shorter time to achieving PASS on KOOS Symptoms and KOOS QOL (HR=1.030-1.043, P=0.001). Greater BMI (HR=0.946, P=0.020) and the number of focal chondral defects (HR=0.083-0.255, P=0.007-0.029) was associated with delayed MCID for KOOS ADL and QOL, respectively, while concomitant realignment surgery decreased time to MCID on KOOS Sports (HR=2.542, P=0.008). Conclusions: This study defined the time to achieving MCID and PASS on IKDC and KOOS subscores for patients undergoing MAT. Worker's compensation status, BMI, and the presence of focal chondral defects may prolong time to achievement of MCID and PASS after MAT. :